ANÁLISE DE GÊNERO SOBRE A INFLUÊNCIA DO CONDICIONAMENTO FÍSICO NA RESPOSTA DO REFLEXO MIOTÁTICO. (Functional Plant Breeding Journal, 2021)
This article highlights the study Gender analysis on the influence of physical fitness on myotactic reflex response. The central objective was to quantify the myotactic reflex response, to analyze the physical fitness of the individuals and the sex of each participant through the standard reflex quantifying the activation of the rectus femoris and vastus lateralis muscles of both limbs. Being a cross-sectional research that analyzes a specific point at a given moment, the present work presents a qualitative approach to the exposed problem. The methodology was to study a group of 20 people, subdivided into: 5 men practicing physical activity and 5 sedentary, 5 women practicing physical activity and 5 sedentary. Individuals must be between 20 and 30 years old and sedentary or not. Results Through the research, the results showed no differences between the analyzed analysis groups, but with the same result, it is evident the new research on the subject with the validation of valid techniques of recovery and recovery techniques, including new studies of training activities. Scenographic and proprioceptive conditions should be maintained.